ФОРМУВАННЯ КОМУНІКАТИВНОЇ КОМПЕТЕНТНОСТІ МАЙБУТНІХ УЧИТЕЛІВ ПІД ЧАС ВИВЧЕННЯ КУРСУ “УКРАЇНСЬКА МОВА (ЗА ПРОФЕСІЙНИМ СПРЯМУВАННЯМ)” (Педагогіка вищої та середньої школи, 2008)
The peculiarities deals rattle some aspects of communication skills development of simple seutence complicated by Participle construction functioning in the text; the peculiarities of in this article as example of the analysis. The author suggests the system of leading and answers for these questions, gives methodical recommendations for conducting the praticat lesson. And all this is for good learning the theme in conditions of credit-module system.